Estratégias de organização do trabalho na atividade leiteira em propriedades de agricultura familiar - Santos Filho, Joel Carneiro dos (2009)
Aiming to analyze the labor organization in family farming, it was done a research with 30 properties with emphasis on milk. These properties are located in the Amusep region. The interviews were semi-structured, guided by a roadmap. From these, 16 variables are built with two to three terms each, having a total of 39 variables. The analysis used was a multivariate statistical technique: the analysis of multiple correlations. In the analysis, the first three factors represented 44.51% of accumulation of inertia. The factors F1, F2 and F3 indicate, respectively, capitalization, and diversification strategy of fertilizer in production systems. The quadrant -F1, -F2 include systems with low technological level. The quadrant -F1, +F2 include systems r lower than others considering the number of people involved, the cows and the effective used area. The quadrant +F1, +F2 include farming concerned about to keep production, fertilized pastures and providing food concentrates. In quadrant + F1, - F2 include more structured systems, with greater and more diverse area. There was done a hierarchical analysis upward, and formed four clusters, and the cases of clusters A, B, C are very different from those of cluster D.